Answer:
see below
Step-by-step explanation:
3t+8(2t-6)=12+14t
Distribute
3t +16t-48 = 12+14t
Combine like terms
19t -48 = 12+14t
Subtract 14t from each side
5t -48 = 12
Add 48 to each side
5t = 60
Divide by 5
t =12
2v+18=16-4(v+7)
Distribute
2v+18 = 16 -4v -28
Combine like terms
2v +18 = -4v -12
Add 4v to each side
6v+18 = -12
Subtract 18 from each side
6v = -30
Divide by 6
v = -5
4x-(9-3x)=8x-1
distribute
4x -9+3x = 8x -1
Combine like terms
7x -9 = 8x -1
Subtract 7x from each side
-9 = x-1
Add 1 to each side
-8 =x
12(3+y)=5(2y+8)
Distribute
36 +12y = 10y +40
Subtract 10y from each side
36+2y = 40
Subtract 36 from each side
2y =4
Divide by 2
2y/2 = 4/2
y =2